Bending Opinion : Essays on Persuasion in the Public Domain - Haaften, Ton van (Book collections on Project MUSE., 2011)
"Rhetoric is, from both a practical and a theoretical perspective, essential to the conduct, analysis and evaluation of public debates. After all, the idea of Democracy is closely intertwined with the ideal of transparent decision-making on the basis of open high-quality discussions in the public domain. From classical antiquity till the present time, methods of organizing and conducting public debate and decision-making by which public speakers can effectively construe their message to persuade or to bend opinions of others have been hotly contested. "Bending opinion" is a collection of essays by distinguished international scholars that presents an overview of the state of interdisciplinary scholarship on the art of rhetoric and the varied approaches and methodologies within it, illustrated with relevant examples and compelling case studies"--Publisher's description